Metode Analisis Dialektika Hegel Untuk Meningkatkan Berfikir Kritis Dan Kreatif Siswa Dalam Pembelajaran Ilmu Pendidikan Sosial - Rohani, Rohani; Fadillah, Fanny Suci; Ernita, Mahdar; Zatrahadi, Muhammad Fahli (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
This analysis describes the 21st Century Critical and Creative Thinking, which describes the Hegelian Dialectical Analysis method by unraveling social science learning in Junior High School. By describing the Hegelian Dialectical Analysis method in theory, the findings got in the theory can improve students’ critical thinking skills in 21st century social studies learning in junior high schools, especially improving students’ critical and creative thinking in social studies learning in junior high schools.Keyword: Creative thinking, dialectical analysis, social studies learning